1994
DOI: 10.1016/0168-6496(94)90069-8
|View full text |Cite
|
Sign up to set email alerts
|

Water flow induced transport of Pseudomonas fluorescens cells through soil columns as affected by inoculant treatment

Abstract: Water flow induced transport of Pseudomonas fluorescens cells through soil columns was measured as affected by the inoculant treatment. Bacterial cells were introduced into the topsoil of columns, either encapsulated in alginate beads of different types or mixed with bentonite clay in concentrations ranging from 0.5 to 5.0% (w/v). Survival of bacterial cells was improved with the use of alginate or bentonite. Transport, as determined by destructive sampling of the columns, was reduced with the use of alginate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, for organic substrates such as manure and slurry, the adsorption and desorption behavior of bacteria are due not only to differences in physical characteristics of the substrate but also to biophysical properties of the organic matter (22). Experiments on the percolation of Pseudomonas fluorescens also showed that application of an adsorption substrate (such as bentonite clay) to the soil may increase survival of P. fluorescens and reduce transport to deeper layers (13). In our experiments, it is likely that some of the organic matter in the slurry moved down the soil profile while manure particles moved less readily.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…However, for organic substrates such as manure and slurry, the adsorption and desorption behavior of bacteria are due not only to differences in physical characteristics of the substrate but also to biophysical properties of the organic matter (22). Experiments on the percolation of Pseudomonas fluorescens also showed that application of an adsorption substrate (such as bentonite clay) to the soil may increase survival of P. fluorescens and reduce transport to deeper layers (13). In our experiments, it is likely that some of the organic matter in the slurry moved down the soil profile while manure particles moved less readily.…”
Section: Discussionmentioning
confidence: 56%
“…However, we were more interested in determining the influence of the manure or slurry application method on the distribution and survival of E. coli O157:H7 and Salmonella serovar Typhimurium in soil columns. Another limitation was that relatively small soil columns were used, which may not be representative of field conditions due to the influence of soil cracks and wall effects on water flow (13). However, only in such controlled experiments is it possible to distinguish the exact influence of certain factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spread of bacteria through soil has implications for the persistence of genetically modi¢ed organisms [7,8] and contamination of groundwater supplies by microorganisms present in sewage from soil-based waste disposal systems [9]. Understanding bacterial movement in soil is also important for manipu-lating colonisation of plant roots [10,11] and for optimising the dispersal of inoculants used in biocontrol and bioremediation strategies [12,13]. Previous studies have investigated the numerous factors a¡ecting movement of bacteria in soil [7,10,14^16] but few have attempted to di¡erentiate between passive spread of bacteria and active motility involving £agella [11,17,18].…”
Section: Introductionmentioning
confidence: 99%